2019
DOI: 10.1021/acsaem.9b01203
|View full text |Cite
|
Sign up to set email alerts
|

Highly Concentrated LiTFSI–EC Electrolytes for Lithium Metal Batteries

Abstract: Concentrated electrolytes have the potential to increase the stability for batteries with lithium metal anodes. In this study, liquid electrolytes were created by mixing ethylene carbonate (EC), a solid at room temperature, with a high concentration of LiTFSI salt. The binary LiTFSI–EC highly concentrated electrolytes have the benefit of extremely low volatility as compared to conventional organic electrolytes and also allow for cycling vs Li metal anodes. Using a LiTFSI–EC electrolyte with molar ratio 1:6, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 44 publications
4
60
0
Order By: Relevance
“…2 mA/cm 2 for both steps), a capacity retention of ~45% was achieved after 50 cycles using 4 M LiFSI in DME electrolyte. Very recently, Nilsson et al 52 studied even higher LFP areal loading cathodes (3.5 mAh/cm 2 ) for anode free cells which is very similar to our cathode configuration. They reported that with a carbonate based organic electrolyte (1.86 M LiTFSI in EC), the LFP Cu cell was stable up to 30 cycles and the first discharge capacity was found ~2.7 mAh/cm 2 with 87% coulombic efficiency at a current density of 1 mA/cm 2 .…”
Section: 'Anode Free' Lfp-cu Cell Cyclingsupporting
confidence: 84%
“…2 mA/cm 2 for both steps), a capacity retention of ~45% was achieved after 50 cycles using 4 M LiFSI in DME electrolyte. Very recently, Nilsson et al 52 studied even higher LFP areal loading cathodes (3.5 mAh/cm 2 ) for anode free cells which is very similar to our cathode configuration. They reported that with a carbonate based organic electrolyte (1.86 M LiTFSI in EC), the LFP Cu cell was stable up to 30 cycles and the first discharge capacity was found ~2.7 mAh/cm 2 with 87% coulombic efficiency at a current density of 1 mA/cm 2 .…”
Section: 'Anode Free' Lfp-cu Cell Cyclingsupporting
confidence: 84%
“…High CE in DOL/DME is typically reported in Cu–Li cells. 19 , 47 Low CE in the DOL/DME electrolyte was however observed in Cu−LFP cells. 47 …”
Section: Resultsmentioning
confidence: 99%
“… 42 , 43 The DOL/DME electrolyte is widely used in Li–S battery research, 44 and the Li deposits have been shown to have a characteristic round-shape morphology. 45 47 In addition, we use the bulk magnetic susceptibility (BMS) effects of Li metal and LFP, performing a careful analysis of the 7 Li NMR shift, to provide insight into the surface coverage and the Li deposit morphology. 48 , 49 The Li metal dissolution that occurs during rest periods was monitored by in situ NMR, the results revealing that the total corrosion of Li (both the chemical SEI formation and galvanic corrosion) remains a major concern for rechargeable LMBs and is expected to be especially important for batteries with a limited amount of Li present in the cell.…”
Section: Introductionmentioning
confidence: 99%
“…A high permittivity solvent, typically ethylene carbonate (EC), is employed to dissociate the salt and a low viscosity co‐solvent, to improve the mobility‐and the ionic conductivity is typically highest at 1 M concentration . In contrast, HCEs, an alternative electrolyte concept which has emerged rather recently, aims mainly to improve on the common LIB electrolyte drawbacks of safety, and electrochemical stability . HCEs may, however, also enable the use of alternative electrolyte salts, solvents, and electrode materials .…”
Section: Introductionmentioning
confidence: 99%